Computational fluid dynamic simulations of granular flows: Insights on the flow-wall interaction dynamics. (December 2022) - Neglia, Francesco; Dioguardi, Fabio; Sulpizio, Roberto; Ocone, Raffaella; Sarocchi, Damiano
Highlights: Topography controls the dynamics and propagation of dry volcanic granular flows. MFIX two-fluid model was used to study the granular flow – wall interaction. Experimentally-generated volcanic granular flows were simulated with MFIX. The solid phase wall boundary condition affects the flow conditions. Abstract: Dry volcanic granular flows are gravity-driven currents composed of solid particles where particle-particle interactions dominate the motion. The interaction with topography is a relevant factor controlling the propagation of such flows. In this paper we investigate the dynamics of channelised volcanic granular flows by comparing large-scale experiments with multiphase computational fluid dynamic simulations using the Two-Fluid Model approach, with an emphasis on the dynamics regulating the flow-wall interactions. We use the software MFIX to carry out sensitivity analysis of the boundary conditions for the solid phase implemented in the numerical code. The sensitivity analysis shows how the choice of the boundary condition and of the relevant parameters controlling the boundary conditions highly affect the dynamics of the whole flow. Finally, a preliminary benchmark of the MFIX boundary conditions with one large-scale experiment is presented, showing good agreement between the simulated and experimental flow front velocities. Grpahical abstract: Image, graphical abstract